1973
DOI: 10.1111/j.1423-0410.1973.tb03535.x
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity of Leukocyte and Platelet Alloantibodies in Sera of Patients with Nonhemolytic Transfusion Reactions

Abstract: To evaluate the relevance of HL-A-specific antibodies in nonhemolytic transfusion reactions, sera from 72 patients with transfusion reactions were examined using platelet microcomplement fixation and microlymphocytotoxicity. Lymphocytotoxic antibodies were found in 24 and platelet complement-fixing antibodies in 18 patients. Thirteen positive sera were studied by absorption and elution with platelets. A total of 103 eluates (mean 7.9 eluates per serum) was tested serologically for antibody specificity. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…In fact, HLA antibodies seem to be more often responsible than granulocyte-specific anti bodies. This supports the results of Heinrich et al [1973], who came to the same conclu sion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, HLA antibodies seem to be more often responsible than granulocyte-specific anti bodies. This supports the results of Heinrich et al [1973], who came to the same conclu sion.…”
Section: Discussionsupporting
confidence: 90%
“…Like other authors [Goodman and Masaitis, 1967;Ahrons, 1971;Heinrich et al, 1973;Nymand, 1969;Décary et al, 1984], we found that the sera of female patients contained a greater diversity of alloantibodies than those of male patients, which can be explained by the additional immunizing in fluence of pregnancy. In fact, all the female patients whose sera were tested had been pregnant (table I).…”
Section: Discussionsupporting
confidence: 87%
“…The problem has been that the sensitivity of the techniques for detecting platelet isoantibodies have been relatively poor. Complement-fixing platelet isoantibodies have been identified in 10-60% of multitransfused patients (3,14,15). Isoantibodies as detected by lymphocytoxicity or other currently available techniques are identified in about 30% of this group of patients (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Wolf and Canale [6] detailed a fatal reaction to a red cell transfusion in a multitransfused thalassémie child with lymphocytotoxic HLA antibodies. Several recent studies have shown that the most common ly found recipient antibodies associated with nonhemo lytic febrile transfusion reactions are not directed towards granulocyte antigens but are lymphocytotoxic, directed against HLA antigens [5,8,9], Interdonor red cell incompatibility in the Kell antigen system has caused reactions of variable severity [19][20][21][22][23]. Interdonor reactions caused by RBC transfusions have been described in which the transfusion of Kell-negative red cells with Kell antibody in donor plasma at the same time as another unit of Kell-positive red cells has caused a hemolytic transfusion reaction when both units were transfused to a Kell-negative patient [19,20].…”
Section: Discussionmentioning
confidence: 99%